Social-Economic Factors Related to Miraa Farming Affecting Retention of Boy-Child in Public Secondary Schools in Mbeere South-Sub County, Kenya - Nderi K. , Rachel; Kimosop , M; Kinyua, J. (African Journal of Education,Science and Technology (AJEST), 2022)
The Government of Kenya, in its efforts to achieve vision 2030, aims at enhancing transition rates in basic education. This effort however is frustrated by increasing dropout rates particularly in public secondary schools which is attributed to a number of factors among them cultural, environmental, school based and socio economic. One of the factors that has been singled out as a cause for increased drop outs in secondary schools is child labour in agricultural farms. The purpose of this study was to establish the socio-economic factors related to miraa farming affecting school retention of boy child in public secondary schools in MbeereSouth Sub-County. The study was guided by the Social Systems Theory as advocated by Shultz. The study employed the survey research design. The location of the study was specifically the miraa growing areas of Mbeere South Sub County. The target population was 160 respondents comprising of be 12 principals, 140 teachers and eight local administrators. The teachers included 12 senior teachers, 48 class teachers, and 80 general subject teachers. The local administrators comprised of two chiefs, two assistant chiefs, two village elders, and two nyumba kumi members. Twelve schools from the miraa growing areas of Mbeere South Sub-County were purposively sampled for the study. Purposive sampling was also employed to select the 12 principals and eight local administrators while stratified random sampling was used to select 36 teachers from specific schools. Teachers were stratified according to their designation in the school as outlined in the target population. A questionnaire was used to collect data from the teachers while interview schedules were used for the principals and the local administrators. Test-retest method was used to establish the reliability of the questionnaire. The reliability test yielded a coefficient of 0.87 which was considered as reliable. Qualitative data was analyzed through content analysis by grouping the data along similar themes as per the objectives of the study. Quantitative data was analyzed using descriptive statistics such as percentages, means and standard deviations and was presented by use of frequency distribution tables. The study found that miraa farming and business contribute to low retention rates of the boy child through offering opportunities of employment to the students. Dropping out is caused by parents’ lack of financial strength to cater for school needs and other levies due to the UK ban of miraa exportation. Secondary school boys are engaged in the miraa farming and business through, tending the miraa trees, harvesting, packaging, transporting, hawking in towns and shopping centers and also preparing the produce to external markets. Based on the findings of the study, the Ministry of Education may develop policies that may streamline the retention of the boy-child in public secondary schools.